Composites for hard tissue repair - Mustafa, Zaleha B.; Tanner, K.E (John Wiley & Sons, Inc., 2012)
Composite implants have been used in fracture fixation since the 1980s. Now filled polymer composites have been developed for applications from ear implants through to tissue engineering. In this article, both degradable and nondegradable composites are considered. The progress of development and some of the test considerations are discussed.